2013
DOI: 10.1177/0363546513495641
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Meniscus Repair and Meniscectomy in the United States, 2005-2011

Abstract: There has been an increased number of isolated meniscus repairs being performed in the US over the past 7 years without a concomitant increase in meniscectomies over the same time frame. These data suggest that meniscus repairs are preferentially being performed over meniscectomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
314
2
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 347 publications
(339 citation statements)
references
References 32 publications
10
314
2
13
Order By: Relevance
“…Also, some patients with degenerative tears have an acute/sudden onset of symptoms with or without a clear knee injury, and these are therefore coded as traumatic (Drosos and Pozo 2004). Based on the current literature, only 5–15% of all treated meniscal tears are traumatic (Metcalf and Barrett 2004, Christoforakis et al 2005, Camanho et al 2006), and according to a report from the USA, 75% of patients undergoing meniscus repair are under 35 years of age (Abrams et al 2013). The incidence of meniscus repairs in our study remained low and unchanged during the study period in both Finland and Sweden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, some patients with degenerative tears have an acute/sudden onset of symptoms with or without a clear knee injury, and these are therefore coded as traumatic (Drosos and Pozo 2004). Based on the current literature, only 5–15% of all treated meniscal tears are traumatic (Metcalf and Barrett 2004, Christoforakis et al 2005, Camanho et al 2006), and according to a report from the USA, 75% of patients undergoing meniscus repair are under 35 years of age (Abrams et al 2013). The incidence of meniscus repairs in our study remained low and unchanged during the study period in both Finland and Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports regarding the trends in a number of knee arthroscopic procedures indicate a reduced incidence of arthroscopies for knee OA, and a steady increase in the number of arthroscopic meniscus surgeries (Hawker et al 2008, Kim et al 2011, Abrams et al 2013). In the UK, the incidence of arthroscopic meniscal resections more than doubled from 2000 to 2012 in patients over 60 years of age (Lazic et al 2014).…”
mentioning
confidence: 99%
“…A multitude of incidence and demographic studies of orthopedic injury have been used the PearlDiver database since 2010. [6][7][8][9][10][11][12][13][14][15][16][17] PearlDiver provided state totals of operatively managed tibia fractures and state totals of patients who have had both a lower extremity fasciotomy and an operatively managed tibia fracture from 2007 to 2011. State procedure volumes less than eleven were censored by PearlDiver to protect patient privacy.…”
Section: Methodsmentioning
confidence: 99%
“…Injury to, or removal of, meniscal tissue may be associated with articular cartilage degeneration, knee instability, and, ultimately, the progression of osteoarthritis. Multiple authors have reported on the potentially devastating implications of meniscal deficiency, and every attempt should be made to preserve meniscal tissue in the setting of meniscus injury, particularly in the young and/or athletic patient population [1]. Unfortunately, damaged meniscus tissue is not always amenable to repair, and meniscectomy is unavoidable.…”
Section: Introductionmentioning
confidence: 99%